A microwave foaming method for fabricating glass fiber reinforced phenolic foam. (15th September 2016) - Choe, Jaeheon; Kim, Minkook; Kim, Jinwhan; Lee, Dai Gil
Abstract: Phenolic foam is a fire-retarding insulator that can endure temperatures of up to 300 °C, and it is carbonized when it is exposed to fire, which decreases its thermal conductivity and prevents the spread of fire. Therefore, phenolic foam has been used for many applications, such as in the architectural and aerospace fields. However, phenolic foam requires blowing agents during the fabrication process, which causes environmental pollution. Therefore, a new foaming method that is environmentally friendly is needed. In addition, due to the brittleness of phenol, a fiber reinforcement method is required to improve the mechanical properties of the phenolic foam. In this study, a new foaming method for fabricating low-density phenolic foam that uses microwaves is developed and optimized. The effect of the viscosity of the phenolic resin and the curing speed on the foam density and uniformity is investigated. To improve the mechanical properties of the phenolic foam, a reinforcement method using chopped glass fiber was optimized with respect to the fiber length and content. The mechanical properties of the fiber reinforced foam were evaluated by measuring the tensile strengths and fracture toughnesses. Finally, the thermal conductivity of the phenolic foam fabricated by the microwave foaming method is measured.